2014
DOI: 10.1111/dsji.12035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differences in Nonteaching Factors Influencing Student Evaluation of Teaching between Engineering and Business Classrooms

Abstract: In recent years, there have been increasing calls from the government and other organizations to provide easy public access to student evaluations of teaching. Indeed, the increasing ease of displaying and viewing large quantities of information, and competition among universities and majors for students, makes it likely that an era of greater transparency of this type of information is at hand. While students' evaluation of teaching (SET) is one quantitative metric that rates the instructor, it may be influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…They found that female students tended to give higher SET scores than male students (Ali & Ajmi, 2013;Al-Issa & Sulieman, 2007;Batten et al, 2013;Beuth et al, 2015;Driscoll & Cadden, 2010;Narayanan et al, 2014;Kozub, 2010;Shauki et al, 2009;Whitworth et al, 2002;Worthington, 2002).…”
Section: Gendermentioning
confidence: 99%
See 4 more Smart Citations
“…They found that female students tended to give higher SET scores than male students (Ali & Ajmi, 2013;Al-Issa & Sulieman, 2007;Batten et al, 2013;Beuth et al, 2015;Driscoll & Cadden, 2010;Narayanan et al, 2014;Kozub, 2010;Shauki et al, 2009;Whitworth et al, 2002;Worthington, 2002).…”
Section: Gendermentioning
confidence: 99%
“…They proposed that different non-instructional factors could affect the results of SET or produce biased results, and called for further studies (Coffman, 1954;Reynolds, 1979). Since then, different studies have been conducted to identify and understand the factors that could affect the results of SET (Abrami, Perry, & Leventhal, 1982;Ali, & Ajmi, 2013;Al-Issa & Sulieman, 2007;Centra, 1977;Frey, Leonard, & Beatty, 1975;Marsh, 1983;Narayanan, Sawaya, & Johnson, 2014;Santhanam & Hicks, 2002;Whitworth, Price, & Randall, 2002;Worthington, 2002). These studies uncovered different factors, which were not related to the dimensions that the SET is trying to measure, which influence the results of SET.…”
Section: Background Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations